P239 Eradication of new pseudomonas aeruginosa isolates in adults with cystic fibrosis. (12th November 2019) - Boyes, WL; McVean, R; Bright-Thomas, RJ
Abstract : Introduction: UK national CF registry data 2017 demonstrates that 44.5% of UK adults with CF are chronically colonised with Pseudomonas aeruginosa (PA). Chronic PA infection, once established, is usually impossible to eradicate and is associated with reduced life expectancy in CF. The aim of this study was to examine eradication rates, PA strain typing, and treatment regimens used following new isolations of PA at a large UK Adult CF Centre. Methods: Data was examined for all patients not known to have chronic PA infection attending a large regional UK CF Adult Centre isolating PA over a 7 year period. Results were gathered using the hospital online results system, clinic letters and national laboratory strain typing reports for 2012 – 2019. Successful eradication was defined as ≥3 sputum samples clear for PA over 6 months with no subsequent isolation of the same strain. Results: 168 patients, not considered chronically colonised with PA were identified. 72 of these isolated PA over the 7-year study period. 19 patients isolated PA on multiple separate occasions resulting in 91 individual PA infection episodes. Examining these episodes in detail: 55/91 episodes were new PA isolates. 46/55 (83.6%) of these successfully eradicated. Unique strains had the highest eradication rate at 20/21 (95.2%), followed by common environmental strains at 19/25 (76.0%) and epidemic (presumed transmissible) strains 3/5 (60.0%). Patients' first PA infection episodes had a higher eradication rate 38/44 (86.4%) than second episodes 7/10 (70.0%). One patient had a third episode and successfully eradicated. 29/91 episodes were identified on strain typing as chronic PA infection: 15/29 (51.7%) were chronic on transfer to the unit and 14/29 (48.3%) had suppressed chronic infection due to long term inhaled antibiotics. The first episode of PA isolation was classed as a failure to eradicate and subsequent episodes as supressed. 7/91 episodes had incomplete data due to transfer or ongoing treatment. Discussion: In adults with CF, eradication rates of new PA isolates are extremely high at our centre but accurate strain typing is essential to distinguish acute from chronic PA infection and unique from epidemic strains.